2000
DOI: 10.1159/000051974
|View full text |Cite
|
Sign up to set email alerts
|

Boerhaave-Mimicking Esophageal Perforation with Subsequent Esophagobronchial Fistula Formation as the Primary Manifestation of Crohn’s Disease

Abstract: Background: Spontaneous ruptures of the esophagus are rare, but may lead to deleterious courses, even if diagnosed early. Case Report: We report a case of Boerhaave’s syndrome-mimicking esophageal perforation due to a stricture of the distal esophagus as the primary manifestation of Crohn’s disease. Diagnosis was delayed resulting in a complicated clinical course. The presented patient is the first case in the literature with esophageal perforation related to a previously undiagnosed Crohn’s disease that lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…3 Often, the diagnosis has been made postoperatively after the onset of severe complications requiring emergency surgery for free perforations or fistulae. 8,9 Consistently with these reports, in our patient with a history of heartburn the diagnosis was made on the specimen of the resected bowel after the third surgical procedure. This occurred several months after the duodenal and esophageal perforation, that were likely due to CD although histology was not available.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…3 Often, the diagnosis has been made postoperatively after the onset of severe complications requiring emergency surgery for free perforations or fistulae. 8,9 Consistently with these reports, in our patient with a history of heartburn the diagnosis was made on the specimen of the resected bowel after the third surgical procedure. This occurred several months after the duodenal and esophageal perforation, that were likely due to CD although histology was not available.…”
Section: Discussionsupporting
confidence: 78%
“…The diagnosis of upper gastrointestinal CD requires a high degree of suspicion due to both the non‐specificity of symptoms such as heartburn, dysphagia, and dyspepsia, and the non‐specificity of radiological and endoscopic findings including mucosal erythema, erosions and ulcers 3 . Often, the diagnosis has been made postoperatively after the onset of severe complications requiring emergency surgery for free perforations or fistulae 8,9 . Consistently with these reports, in our patient with a history of heartburn the diagnosis was made on the specimen of the resected bowel after the third surgical procedure.…”
Section: Discussionsupporting
confidence: 73%
“…In the clinical view, dysphagia and weight loss were the most typical symptoms in the first case, whereas in the third heartburn and odynophagia were observed. Endoscopy of the upper gastrointestinal tract can reveal the following lesions in the oesophageal region: irregular reddening or aphthous, or swollen folds of the mucous membrane, deep linear ulcerations located in the whole oesophageal mucous (which in fact is extremely rare) and strictures or fistulas [9,17]. Yekebas et al reported a case of oesophageal perforation due to a stricture of the distal oesophagus as the primary manifestation of CD [17].…”
Section: Leki Stosowane W Terapii Choroby Leśniowskiego-crohnamentioning
confidence: 99%